Analisis Dan Perancangan Sistem Informasi Manajemen Proyek Berbasis Web Pada CV. Radityatama Engineering Konsultan - Akbar, Niko; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
On Project Work. Each process reports the Overseer will record project development data, then Supervisor Engineering checks the existing data and makes the project development volume. The supervisor then contacts the admin by telephone to submit project development data and the data will be entered into Microsoft Office Excel as project development data. And the data that has been inputted by the admin will be seen by the project manager to see the results of project development by project workers and manage existing work plan data. E very time it is done it makes time reporting inefficient. With these considerations, the need for solving problems related to Web-Based Project Management Information Systems using UML (Unified Modeling Language) system modeling methods using Case Diagrams, Activity Diagrams and class Diagrams. In this research, creating data that manages employee data, manages client data, manages project activity data, manages project payment data, manages project process data, manages project document data, manages office data inventory and manages reports. Hope with the Project Management Information System, CV. Radityatama Engineering Consultants can Facilitate Their Performance in Recording Project Development Reports to Company Managers and Directors.